Characterization of thoracic motor and sensory neurons and spinal nerve roots in canine degenerative myelopathy, a potential disease model of amyotrophic lateral sclerosis. Issue 4 (21st December 2013) - Morgan, Brandie R.; Coates, Joan R.; Johnson, Gayle C.; Shelton, G. Diane; Katz, Martin L.
<x xml:space="preserve">Abstract</x> Canine degenerative myelopathy (DM) is a progressive, adult‐onset, multisystem degenerative disease with many features in common with amyotrophic lateral sclerosis (ALS). As with some forms of ALS, DM is associated with mutations in superoxide dismutase 1 (SOD1). Clinical signs include general proprioceptive ataxia and spastic upper motor neuron paresis in pelvic limbs, which progress to flaccid tetraplegia and dysphagia. The purpose of this study was to characterize DM as a potential disease model for ALS. We previously reported that intercostal muscle atrophy develops in dogs with advanced‐stage DM. To determine whether other components of the thoracic motor unit (MU) also demonstrated morphological changes consistent with dysfunction, histopathologic and morphometric analyses were conducted on thoracic spinal motor neurons (MNs) and dorsal root ganglia (DRG) and in motor and sensory nerve root axons from DM‐affected boxers and Pembroke Welsh corgis (PWCs). No alterations in MNs or motor root axons were observed in either breed. However, advanced‐stage PWCs exhibited significant losses of sensory root axons, and numerous DRG sensory neurons displayed evidence of degeneration. These results indicate that intercostal muscle atrophy in DM is not preceded by physical loss of the motor neurons innervating these muscles, nor of their axons. Axonal loss in thoracic sensory roots and sensory neuron death suggest that sensory involvement may play an important role in DM disease progression. Further analysis of the mechanisms responsible for these morphological findings would aid in the development of therapeutic intervention for DM and some forms of ALS. © 2013 Wiley Periodicals, Inc.